Pengaruh Sikap, Pengetahuan Dan Keahlian Terhadap Kinerja Karyawan Pada PT. Bhanda Chara Reksa (Persero) Kabupaten Ende - Sere, Yosep; Tanusi, Gabriel; Langga, Lambertus (Program Studi Manajemen Universitas Flores, 2021)
This study aims to determine the effect of attitude, knowledge and expertise against employee performance at PT. Bhanda Ghara in Ende Reegency. The type of research used is causality research with a quantitative approach. The data analysis technique used is multiple linear regression analysis. The population in this study consisted of 32 people and a sample of 32 people and a sample of 32 people obtained from the entire number of the popukation. From the results of the development and testing of the instrument has been produced a good questionnaire tool (qualifies validity, reliability). From result t statistic test for attiude and skill variables has value > and significance value <0,05, and variable knowledge has a value of < significance value> 0,05. This matter shows rhat the attitude and skill relationship variables have a significant effect on employee performance, while the knowledge variables has no effect on employee performance, while the knowledge variable has no effect on employee performabce. On the results of the Ftest, with a value of 16,461 > Ftable = 2,95 and the value of significance < 0,05. This shows that the attitude variable (X1), knowledge (X2), and expertise (X3) simultaneously affect employee performance (Y). for the adjusted R Square value of 0.599 or 60%, this shows that the percentage of the influence of attitudes, knowledge and skills on employee performance by 60%. While 40% is influenced by other unexplained factors in this research